Safety and Efficacy of Endovascular Treatment on Pregnancy-Related Iliofemoral Deep Vein Thrombosis - Zhao-Xuan Lu MD; Heng-Le Wei MD; Yadong Shi MD; Hao Huang MD; Haobo Su PhD; Liang Chen MD (Clinical and Applied Thrombosis/Hemostasis, 2022)
Objective : This study investigates the safety and efficacy of endovascular treatments on pregnancy-related iliofemoral deep vein thrombosis (DVT). Methods : We retrospectively reviewed data of 46 patients who had symptomatic pregnancy-related iliofemoral DVT and underwent endovascular treatment. The patients treated with catheter-directed thrombolysis (CDT) were classified as the CDT group. In contrast, those treated with CDT combined with pharmacomechanical thrombectomy (PMT) or angioplasty/stenting were classified as the pharmacomechanical catheter-directed thrombolysis (PCDT) group. Results : Based on the immediate post-operative clot burden reduction rate analysis of 46 patients: 22 cases were completely dissolved (lysis grades III), 12 were partially dissolved (lysis grades II), and 12 failed (lysis grades I). There was a statistically significant difference in the rate of clot burden reduction between the CDT group (n = 19) and the PCDT group (n = 27) ( p  = 0.001). There was no statistically significant difference in the number of bleeding events between the two groups ( p  = 0.989). At 24 months, cumulative venous patency in the CDT group was 50.0%, compared to 78.2% in the PCDT group. Furthermore, there was a statistically significant difference in Villalta score (p  = 0.001) and venous severity scoring (VCSS score) (p  = 0.005) between the two groups. Conclusions : CDT treatment combined with PMT or angioplasty/stenting is comparatively safe and effective for pregnant-related DVT patients. PCDT outperforms CDT in terms of immediate efficacy and reduces the incidence of post-thrombotic syndrome with better midterm outcomes.